PENGARUH MEDIA FILM TERHADAP HASIL BELAJAR PESERTA DIDIK - Afdol, Abdul; Mahruddin, Amir (Universitas Djuanda, 2015)
The problem identified in this study is the difference that caused student learning outcomes vary greatly, formative test results are very low, the lack of using media in learning, and learning more using the lecture method. The limitation of this study is a problem in the Media Film effect toward studentsâ outcomes on learning Islamic Education in Fourth Grade of Elementary School at District Cilangkap 5, Depok. Thus, in relation to the restriction of the above problems, the formulation of the problem is